Release Kinetic of Riboflavin from Composite Gel Beads Consisting of Alginate Incorporated with Whey Protein or Xanthan Gum - Wichchukit, Sukanya (Srinakharinwirot University Engineering Journal, 2020)
This research aimed to study the release of riboflavin from composite hydrogel beads in simulated gastric fluid (SGF) and simulated intestinal fluid.(SIF) The combinations of gel bead were 100% alginate, 62% alginate and 38% whey protein, 50% alginate and 50% whey protein, 62% alginate and 38% xanthan gum and 50% alginate and 50% xanthan gum. The cross linking solutions were mixtures of calcium chloride with 0%, 0.25% and 0.5% chitosan. The result showed that 100% alginate beads elicited good forming with homogeneous size and shape. Adding whey protein and xanthan gum to alginate improved riboflavin captivation and slow release. Comparison of fitting with 7 release models, release kinetics of the beads could be explained by Higuchi model, Korsmeyer-Peppas model, and Weibull model. The release mechanism was governed by a combination of diffusion and bead erosion.